"It doesn't matter because I love you". A case study examining the interpretation of Behaviour Classification Tables and Positive Behaviour Support models. Issue 2 (2nd April 2020) - Blanco-Bayo, Alicia
ABSTRACT: The prescriptive outline that guides teachers on the use of Behaviour Policies (BP) omits to suggest whether BPs in Primary schools can be contextualised. This study explores to what extent Behaviour Classification Tables (BCTs) help staff choose strategies to improve behaviour. Using Context-Mechanism-outcome configuration (CMO) as the main structure for a realist analysis, this evaluation examines how the flexibility to interpret BCTs enables staff to support children throughout the school. Whilst the positive impact of adapting BCTs is recognised, it is also highlighted that a strict interpretation of behavioural expectations can hinder the improvement of behaviour. The benefits of using some aspects of the Positive Behaviour Support model (PBS) are identified through the analysis of one case study in a small school in the North West of England. Further research is suggested to design a model that sets behavioural expectations according to developmental needs and might be contextualised according to specific circumstances of individual schools. It is recommended that BCTs might be presented using colour coded diagrams and pictures to develop through illustrations an accessible definition of acceptable behaviour.